2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.24885
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Teaming and Cognitive Style on Student Perceptions of Design Ideation Outcomes

Abstract: She teaches design studios and lecture courses on developing creativity and research skills. Her current research focuses on identifying impacts of different factors on ideation of designers and engineers, developing instructional materials for design ideation, and foundations of innovation. She often conducts workshops on design thinking to a diverse range of groups including student and professional engineers and faculty member from different universities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Numerous techniques developed over the last half century help facilitate concept generation (Helm et al 2016;Jablokow et al 2015;Bohm et al 2005). These techniques can be broadly classified as either structured or unstructured (Gero et al 2013;Moon Sungwoo et al 2012;Shah et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous techniques developed over the last half century help facilitate concept generation (Helm et al 2016;Jablokow et al 2015;Bohm et al 2005). These techniques can be broadly classified as either structured or unstructured (Gero et al 2013;Moon Sungwoo et al 2012;Shah et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Their results suggest that as the cognitive gap between team members increases, the more adaptive team member tends to feel that they contributed less to team ideation, while the more innovative team member tends to feel that they contributed more. In other previous work by Jablokow et al [21], the results suggest that the presence of more innovative individuals on a team may be correlated with a greater occurrence of unique ideas in the team, where unique was defined as new to the current team discussion. They also found that more innovative teams (by KAI mean) tended to exhibit team interactions with a higher degree of integration between topics.…”
Section: Cognitive Style Diversity and Design Teamsmentioning
confidence: 51%
“…In contrast, more innovative individuals prefer less structure, with less concern about consensus, and tend to make radical changes that may ignore rules in an attempt to make the current system work "differently"; their efforts may or may not lead to improvements in that system. Kirton's A-I cognitive style influences both individual problem-solving characteristics and team interactions, and its effects have been studied in observations of engineering teams [22,24,25,21]. However, it is unclear how KAI style could be used to inform the formation of engineering teams.…”
Section: List Of Symbolsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this information doesn't provide a robust way to estimate characteristics of the participants that might lead to interpersonal issues or synergistic team combinations. Specific psychometrics that are impactful in teams and may be of use for building a more nuanced model of team performance here include: personality, using a five-factor model for instance (Salleh, Mendes, Grundy, & Burch, 2009, 2010; cognitive style, a measure of an individual's preferred approach in solving problems (Buffinton, Jablokow, & Martin, 2002;Jablokow, Teerlink, Yilmaz, Daly, & Silk, 2015); and cognitive level, commonly referred to as expertise or knowledge (Ehrlich & Chang, 2006;Faraj & Sproull, 2000).…”
Section: Limitationsmentioning
confidence: 99%